(untitled) (Journal of the College of Basic Education, 2025)
Orientalists - of all kinds - were interested in studying the biography of the Messenger of God, Muhammad bin Abdullah (may God bless him and his family), in all its details, from the political and economic aspects, as well as the social aspects, considering the change this axis brought about in social life between the Arabs in particular and the world in general, and that is what was known About the nomadic life of Arabs and not giving social life much importance, especially women and their participation in social life, In contrast to what the Prophet Muhammad (may God’s prayers and peace be upon him and his family) brought about consolidating the role of women in social life, through Islamic legislation for that, orientalists have shed light on these axes, including the participation of the Messenger of God Muhammad (may God’s prayers and peace be upon him and his family) in family life, and the issue of The polygamy that God Almighty has singled out for her alone, beyond the number permitted in Islamic law, and the issue of women’s education and an explanation of the importance of this aspect in public life. This is done by explaining the most important different opinions of the Orientalists, between supporters, fanatics, and opponents. It has become clear that there is a development in the Orientalist perspective on the life of the Prophet from what it was in previous centuries, approaching moderation and fairness.